(untitled) (Journal of Foreign Language Studies, 2024)
English as a medium of instruction (EMI) has been popularly applied in higher education contexts in Vietnam. EMI lecturers have to face many challenges in terms of language proficiency and content knowledge. This qualitative study aims to examine how much the English for Specific Purposes (ESP) and content lecturers collaborate to help each other overcome such difficulties in the EMI context. Interviews were conducted with seven EMI lecturers at a university in Central Vietnam. The findings showed that there was a lack of collaboration between ESP and EMI lecturers although the participants were aware of its necessity as one of the best solutions for enhancing both English competence and content knowledge. The study also suggests some ways to practice continuous collaboration as a professional development activity.